Chronicle of international labor jurisprudence 2019 - Arias Domínguez, Ángel (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
During the reference period, no relevant resolutions of the Committee on Freedom of Association have been issued, nor has the ECtHR ruled on matters affecting the Spanish state. However, we do have numerous resolutions of the CJEU that affect the Spanish state that we are going to present, along with three resolutions of the Court that affect other legal systems that we also reviewed for your interest.The STJUE of January 22, 2019 [C-193/17] Cresco Investigation GmbH and M.A., addresses a problem of religious discrimination because the legal system grants an additional day off from work to members of certain religious denominations. Even without affecting the Spanish legal system, it has been considered interesting to comment on it.The ATJUE of March 19, 2019 [C-293/18] CCOO of Galicia and the University of Santiago de Compostela, questions the adequacy of a national law that does not provide for compensation for termination of employment contract in terms of employment predoctoral for research tasks.In the STJUE of March 26 [C-377/16] Kingdom of Spain c. European Parliament, the legality of a job offer from Parliament is being debated, which requires that candidates only know German, English or French as a second language.The STJUE of April 11, 2019 [C-29/18, C-30/18 and C-44/18] Cobra Servicios c. J. D. Sánchez and others, deals with a well-known topic, the different compensation that comes from the termi nation of employment contracts of different nature, for the termination of a contract for those of related work or service, and for economic reasons for those of a fixed nature.The STJUE of May 8, 2019 [C-161/18] Villar Láiz c. INSS and TGSS, deals with indirect discrimination based on sex caused by the norm that regulates the calculation of the part-time pension.The very interesting, although ineffective given the legislative amendment made between the approach to the issue and its resolution, STJUE of May 14, 2020 [C-55/18] Federation of Services CC.OO. c. Deutsche Bank addresses a compromised issue, the control of working hours using a mechanism designed solely for the control of overtime.The ATJUE of June 12, 2019 [C-367/18] María Teresa Aragón Carrasco and others c. The State Administration understands that the community law does not contradict the internal norm that does not sponsor any compensation for the termination of possible trust contracts.The STJUE of June 20, 2019 [C-72/18] Daniel Ustariz Aróstegui c. disc. Education The Government of Navarra appreciates that the establishment of an economic supplement linked to the status of civil servant in the education sector is contrary to Community regulations.Anti-discrimination guardianship for pregnancy is not the patrimony of the national order. It has a new version with the STJUE of June 20, 2019 [C-404/18] Jamina Hakelbracht and Tine Vandenbon c. WTG Retail BVBA, in which the normative guardianship is granted to an informal witness of the process of not hiring a worker for being pregnant.Although the STJUE of September 11, 2019 [C-397/8] DW c. Nobel Plastiques Ibérica its relevance due to the suppression in our legal system of the objective dismissal for absenteeism. Nobel Plastiques Ibérica analyzes whether absences from work due to illness related to the disability suffered by the worker can be considered computable for the purposes of objective dismissal due to absenteeism.In the STJUE of September 18, 2019 [C-366/18] Ortiz Mesonero c. UTE Luz Madrid, it was discussed whether the worker who works in a shift company can choose to join the morning shift in order to favor the reconciliation of family and work life.The ATJUE of October 15, 2019 [C-439/18 and C-472/18] OH and ER c. AEAT considers unreasonable the exclusion of periods not worked by permanent-discontinuous workers from the calculation of seniority for the purposes of receiving remuneration supplements.The interesting STJUE of November 7, 2019 [C-396/18] Gennaro Cafaro c. DQ studies an always interesting topic such as employment discrimination on the grounds of age, and although it does not affect the Spanish law, it has been considered appropriate to deal with it.The STJUE of December 5, 2019 [C-398/18 and C-428/18] Bocero Torrico and Fritz Bode c. INSS and TGSS deals with the minimum amount of early retirement, understanding that the Union regulations preclude the granting of this requirement that its amount must be higher than what it would receive when it reached the ordinary retirement age.The last annotated sentence of this year is the STJUE of December 12, 2019 [C-450/18] WA c. INSS that understands that the maternity supplement devised by the LGSS to complement the benefits of women who have been mothers must be interpreted in the sense of not excluding from their receipt men who are in the same situation.
Keywords: Labor discrimination on religious grounds; compensation for completion of predoctoral contract for research tasks; discrimination on linguistic grounds in recruitment by the European Union